Pelatihan Penggunaan Aplikasi Mendeley dalam Penulisan Karya Ilmiah kepada Mahasiswa Pascasarjana di Sekolah Tinggi Teologi Kingdom Bali - Roesmijati Roesmijati; Eddy Salim; Josiharu Edmund Franky (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Reference management is an important aspect of scientific writing, especially for postgraduate students who are required to produce academic work that meets scholarly standards. In practice, many students still struggle to create citations and bibliographies systematically because they have not used reference management software effectively. One application that can assist with reference management is Mendeley. This Community Service Program aims to improve postgraduate students' knowledge and skills in using the Mendeley application for scientific writing and to support the improvement of the quality of academic publications in higher education. The activity was conducted as training, consisting of lectures, demonstrations, and hands-on practice, including program installation, feature introductions, reference management, the use of plugins in Microsoft Word, and the automatic creation of citations and bibliographies in various citation styles. The participants were postgraduate students who were preparing research proposals, theses, or scientific articles. Evaluation was conducted through observation, discussion sessions, and questionnaires to determine participants’ level of understanding and satisfaction. The results showed that the training improved participants’ ability to manage references more effectively, quickly, and systematically. Participants found it easier to create citations, organize references, and compile bibliographies in accordance with required styles, while also reducing writing errors and saving time. Follow-up activities include online mentoring, training modules, and periodic workshops to ensure sustainable benefits and to support a more professional academic writing culture.